La Ilustración como desafío para nuestro presente: algunas notas acerca de la Ilustración en Alemania - Vázquez Lobeiras, María Jesús (2023)
This paper develops a historiographic approach to the development of Enlightenment in Germany, considering its specific traits in comparison to England and France, as well as its different stages. I also present the typology of its main ideas developed by Norbert Hinske, and discuss the possible relevance and significance of these ideas for our current times, specially analysing the idea of a universal human reason and the vocation of human beings.